Indirect field oriented control and parameters identification of three phase ac induction motors - Ang, Tony Yeow Lye (2016)
This dissertation presents the modelling and control of three phase AC induction motor by an electric variable speed drive. The motivation is to verify and further improve understanding of the control methodology employed by variable speed drive. AC three phase induction motor is the workhorse of our modem day. It is primarily used to drive rotating equipment such as fans, pumps and compressors which exhibit quadratic speed versus torque load profile. As such their energy consumption is significantly increased with their operation speed. Performing speed control to their driver, AC three phase induction motor, to align to their required operation speed therefore translates into energy saving. Due to its robustness and development of control methods AC three phase induction motor has also gain significant inroad to dynamic application such as servo, rolling mill and paper machines which was predominated by DC motors. Control of AC three phase induction motor involves controlling the torque it produced as well as its rotating speed. Its non-linear characteristic complicates the development of effective control methodology especially in the field of dynamic application. Vector control, also commonly refers to as Field Oriented Control (FOC), had been developed and commercialised. It had proved to be highly effective for controlling AC motors. Its key concept is emulation of DC motor control. Assumptions and approximations were made in its implementation. These in tum attracts continuous research effort to improve it. Using Matlab simulation, this dissertation reconsolidates and harness the formulation of FOC through verification of its most successful and popular subclass, Indirect Field Oriented Control (IFOC). The high dependency on motor parameters’ accuracy for IFOC is also investigated and analysed. Developed methods used to identify them are presented. Among them Matlab simulations are performed to investigate an offline method. Realising the effect of inverter switching dead time has on automatic motor parameters’ identification process, a strategy is proposed to overcome it.